The cognitive effects of listening to background music on older adults: processing speed improves with upbeat music, while memory seems to benefit from both upbeat and downbeat music - Bottiroli, Sara; Rosi, Alessia; Russo, Riccardo; Vecchi, Tomaso; Cavallini, Elena (Frontiers in Aging Neuroscience, 2014)
Background music refers to any music played while the listener is performing another activity. Most studies on this effect have been conducted on young adults, while little attention has been paid to the presence of this effect in older adults. Hence, this study aimed to address this imbalance by assessing the impact of different types of background music on cognitive tasks tapping declarative memory and processing speed in older adults. Overall, background music tended to improve performance over no music and white noise, but not always in the same manner. The theoretical and practical implications of the empirical findings are discussed.